Gata2is a tissue-specific post-mitotic selector gene for midbrain GABAergic neurons - Kaia Kala; Maarja Haugas; Kersti Lilleväli; Jordi Guimerá; Wolfgang Wurst; Marjo Salminen; Juha Partanen (2008)
Midbrain GABAergic neurons control several aspects of behavior, but regulation of their development and diversity is poorly understood. Here, we further refine the midbrain regions active in GABAergic neurogenesis and show their correlation with the expression of the transcription factor Gata2. Using tissue-specific inactivation and ectopic expression, we show that Gata2 regulates GABAergic neuron development in the mouse midbrain, but not in rhombomere 1, where it is needed in the serotonergic lineage. Without Gata2, all the precursors in the embryonic midbrain fail to activate GABAergic neuron-specific gene expression and instead switch to a glutamatergic phenotype. Surprisingly, this fate switch is also observed throughout the neonatal midbrain, except for the GABAergic neurons located in the ventral dopaminergic nuclei, suggesting a distinct developmental pathway for these neurons. These studies identify Gata2 as an essential post-mitotic selector gene of the GABAergic neurotransmitter identity and demonstrate developmental heterogeneity of GABAergic neurons in the midbrain.